Universitas Klabat Performance Efficiency: A Data Envelopment Analysis - Walean, Ronny Hansje (JBE (Journal of Business and Economics), 2010)
Keen competition in the tertiary educational sector in Indonesia, forced institution to constantly seeking ways of improving productivity and efficency performance in order to survive from the competition. If Institution could offer good quality of product, it will enhance its competitiveness in the marketplace. This study focused on the performance efficiency of Universitas Klabat. The time period of analysis was 1993 to 2003, using the Data Envelopment Analysis (DEA)-Malmquist. This study identified the sources of technical efficiency and total factor productivity performance (TFP). There were three (3) inputs and four (4) outputs to evaluate the Universitas Klabat's efficiency and productivity. The institution's outputs were (a) number of students enrolled, (b) number of graduates, (c) total revenues, and (d) total assets. Inputs used were (a) total operating expenses, including salaries and wages, (b) number of academic staffs (full-time equivalent), and (c) number of non-academic staffs (full-time equivalent). DEA findings revealed that productivity of Universitas Klabat is highly correlated to technological change. Therefore, the theoretical contribution of these results is that the total factor productivity has a direct relationship with the technological change as evident in that the TECHCH sore was 1.027 (2.7 percent growth per year). Technical efficiency or managerial efficiency change was pegged at the value of 1.00